Gastric Outlet Obstruction as a First Symptom of a Non‐Muscle Invasive Bladder Cancer (NMIBC) Progression—A Case Report - Duje Apostolski; Florian Roitner (Cancer Reports, 2024)
ABSTRACT Background Metastatic disease of a urinary bladder cancer localized in the upper abdomen is very rare. This case report describes the first patient with a urinary bladder cancer progression, initially presenting as a gastric outlet obstruction due to peritoneal carcinomatosis. Case We present the case of a 78‐years‐old male patient who was admitted to Hospital St. Josef Braunau in Austria with persistent vomiting. In the medical history, the most prominent finding was a diagnosed high‐risk NMIBC. At the time, patient was between 2. and 3. BCG maintenance instillation cycle, following two transurethral resections. Routine follow‐up cystoscopy 1 month before admission to our department showed no evidence of disease recurrence. Due to the therapy resistant vomiting, gastroscopy was performed, revealing duodenal stenosis without mucosal changes. Subsequently performed abdominal CT‐scan showed homogenous swelling of the mesenteric fat tissue around duodenum, spreading retroperitoneal to both kidneys. In the absence of the typical peritoneal carcinomatosis features, the finding was firstly described as an inflammation of mesenteric fat or panniculitis mesenterialis. Further deterioration of patient's condition and later occurred bilateral hydronephrosis raised a suspicion of peritoneal carcinomatosis. Consequently, conducted laparoscopic exploration confirmed the suspicion describing the tissue conglomerate typical for peritoneal carcinomatosis surrounding the duodenum. Pathohistological analysis of taken samples proved urothelial cancer cells, confirming the diagnosis of metastatic bladder cancer disease. Conclusion This case report presents a very unusual presentation of metastatic urinary bladder cancer that could help clinicians to consider this diagnosis when encountering similar clinical features.